Cortical alpha oscillations as a tool for auditory selective inhibition - Strauß, Antje; Wöstmann, Malte; Obleser, Jonas (Frontiers in Human Neuroscience, 2014)
Listening to speech is often demanding because of signal degradations and the presence of distracting sounds (i.e., “noise”). The question how the brain achieves the task of extracting only relevant information from the mixture of sounds reaching the ear (i.e., “cocktail party problem”) is still open. In analogy to recent findings in vision, we propose cortical alpha (~10 Hz) oscillations measurable using M/EEG as a pivotal mechanism to selectively inhibit the processing of noise to improve auditory selective attention to task-relevant signals. We review initial evidence of enhanced alpha activity in selective listening tasks, suggesting a significant role of alpha-modulated noise suppression in speech. We discuss the importance of dissociating between noise interference in the auditory periphery (i.e., energetic masking) and noise interference with more central cognitive aspects of speech processing (i.e., informational masking). Finally, we point out the adverse effects of age-related hearing loss and/or cognitive decline on auditory selective inhibition. With this perspective article, we set the stage for future studies on the inhibitory role of alpha oscillations for speech processing in challenging listening situations.